Peningkatan Kesadaran dan Dukungan Keluarga Terhadap Kebutuhan Spiritual Pasien Stroke - Permata Sari, Rebbi; Revi Neini Ikbal (Jurnal Pengabdian Ilmu Kesehatan (JPIK), 2025)
Stroke is one of the world's major health problems and is a major cause of disability and premature death, especially in developing countries such as Indonesia. Spiritual problems experienced by stroke patients are actually as important as physical problems. This awareness needs to be built in patients and their families.Family support in fulfilling spiritual needs by motivating for healing by inviting clergy to guide the patient's spirituality. The family can also provide assurance to the patient that the illness suffered is a trial to test faith and fortitude. The purpose of Community Service is toIncreasing family awareness and ability to meet the spiritual needs of stroke patients. The type of activity is Community Service with the method currently used is the audiovisual method, namely the presentation of material using public posters accompanied by oral explanations and distribution of leaflets and evaluation using questionnaires. This Community Service was carried out in the X Health Center Working Area in October 2024 - February 2025. Participants in this activity were families of stroke sufferers. The results of this community service activity showed an increase in knowledge about family awareness and support for spiritual needs in stroke care, from 65% to 85% after the intervention. It is hoped that this activity will accelerate recovery and improve the quality of life of stroke patients.